Service quality towards customer persistency of life insurance scheme, MAA Assurance Berhad: A case study in Cemerlang Agency, Seremban branch / Anis Sabrina Mohd Sabaruldin - Mohd Sabaruldin, Anis Sabrina (Faculty of Business and Management, 2006)
The insurance industry stands poised on the threshold of a new era. With the 1996 Act in place and with the pace of liberalization increasing as the next round of negotiations on General Agreement on Trade in Services ( GATS) commences in mid 1997, it has become vital for the insurers individually and the industry as a whole to map out an appropriate master plan to help chart its future direction. With the combined commitment and efforts of all involved, Bank Negara Malaysia (BNM), the insurers, the trade associations, the insurance brokers, adjusters and agents, and the customers too, the insurance industry can look to a bright future on the back of sustained strong economy and favorable prospects in the emerging markets around the region. Therefore, it is equivalent to this research in order to precisely study the service quality needed in insurance business, in this case of Cemerlang Agency, MAA Assurance Berhad. This study was to focus on the goal of improving and maintaining the service quality of Cemerlang Agency. Furthermore, it is to find out the level of efficiency towards customer service and how far customers are satisfied with the service provided by Cemerlang Agency, MAA Assurance. This study was based on the topic of customer's persistency rate, customer service, customer satisfaction, and dimensionality of service quality, which are taken from various journals of marketing, services, retailing, marketing research, insurance services and the Internet. The scope of study involves 100 respondents, which were randomly selected in Seremban. The questionnaires distributed were modified from the SERVQUAL instrument, and consists of 32 items rated on a 5-point Likert scale. All data were analyzed by using frequency analysis, descriptive statistics and Cross Tabulation. The results indicated that overall the customers were satisfied by the service quality of Cemerlang Agency, but there are certain areas that need improvisation and adjustments. Several recommendations were suggested to help Cemerlang Agency give better service quality and increase their customer's persistency rate.